Paragraph Hamburgers Strategy in Writing a Report Text - Azizah Husda; Ribka Simorangkir; Christine Natalie Zalukhu; Armitha Miranda Marbun; Lorenzo Bindunose Nababan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The purpose of this study was to determine whether employing the paragraph hamburger strategy on the students’ writing report text at SMK Immanuel Medan in the academic year 2022-2023. The writers used the quantitative method when carrying out this research. After doing this research, the writers got several findings. Significant changes are made to students writing abilities after they are trained by using the paragraph hamburger strategy to learn writing skills. The results of this study allow it to be said that applying the paragraph hamburger strategy could have a significant effect on the student’s writing skills. Using the paragraph hamburger Strategy gave a more effective result than using a conventional strategy. The average scores from intensive classes were higher than the average from regular classes.  From this pretest, the average test result from the regular class was 63.86, and after doing that post-test, the mean scores were 73.18. Meanwhile, the pretest was completed by the intensive class, and the mean result was 66.00, and upon completion of the post-test, these mean scores were 82.80. The writers used the t- test to obtain the findings of this study. We might therefore say that the value was 5.64. After analyzing this data, the t-table was smaller than the t-t-test (1.67 > 5.64). That author displays a p-value of 0.05. The DF was 47. By seeing the data, the writers could conclude that the paragraph hamburger strategy could have a significant effect on the students’ report text in SMK Immanuel Medan. From this study, it might be said that Paragraph Hamburger had a big impact on the text written for a student report at SMK Immanuel Medan.